An Analysis of The Body Mass Index (Quetelet Index) of Technical Personnel in Higher Education Institutions of Qarshi City - Khakimovna, Karimova Mavluda; Tura qizi, Juraeva Mohichehra (American Journal of Bioscience and Clinical Integrity, 2026)
This article is about assessing the health status of technical staff working in Karshi higher education institutions and examining the indicators of the Ketle index. In the course of the study, based on the height and weight of technical personnel of Karshi State University and Karshi State University, body mass index is determined, cases of overweight, obesity or underweight are analyzed. Based on the results obtained, recommendations will be developed on the formation of a healthy lifestyle, increasing physical activity and proper nutrition among technical personnel. This study has important implications for the health promotion and disease prevention of higher education workers.